Incidence and risk factors of nephritis in childhood Henoch-Schonlein purpura - Yaulia Yanrismet; Eka Laksmi Hidayati; Zakiudin Munasir; Klara Yuliarti; Afifa Fahriyani (Paediatrica Indonesiana, 2023)
Background Henoch-Schönlein Purpura (HSP) is the most common systemic vasculitis disease in children. It is characterized by involvement of the skin, joints, gastrointestinal tract, and kidney. Kidney manifestations may progress to severe nephritis, even lead to end-stage kidney disease. Objective To identify the incidence and risk factors of nephritis in childhood HSP. Methods A retrospective cohort study was performed to evaluate clinical, demographic, laboratory, and therapeutic parameters of HSP patients aged 0-18 years between 2011-2019 at Dr. Cipto Mangunkusumo Hospital, Jakarta. Diagnoses of HSP were made according to the 2008 EULAR/PRES/PRINTO criteria. Wefollowed subjects’ medical records for at least 3 months after disease onset to observe incidence and risk factors of Henoch-Schönlein nephritis (HSN).Results There were 112 HSP patients (aged 2-17 years) included in this study. HSN was found in 40 out of 112 patients (35.7%). Nephritis developed within the first 4 weeks for a majority of cases. Multivariate analysis showed that persistent purpura (OR 3.306; 95%CI 1.315 to 8.315; P=0.011) and acute phase leukocytosis(OR 2.585; 95%CI 1.047 to 6.385; P=0.039) were significantly associated risk factors for HSN. We found that corticosteroid use did not reduce the risk of HSN. The accumulation of several risk factors was associated with the likelihood of developing HSN. Conclusion Persistent purpura and acute phase leukocytosis are independent risk factors for HSN. Therefore, blood tests are needed to estimate the risk of HSN. Early corticosteroid therapy do not reduce the risk of kidney impairment.